Safety Policy for the Delivery of COVID-19 Infectious Materials - Budiyanto, Budiyanto; Sutrisno, Edy; Asropi, Asropi (KnE Social Sciences, 2022)
A crucial aspect that needs to be considered in handling the COVID-19 pandemic is the process of delivering and receiving infectious materials. The method of packaging and sending infectious materials must conform to the standards and regulations of the transport of dangerous goods to minimize the risk of exposure to the sender, carrier, recipients, the public and the environment. This study aimed to identify inhibiting factors and develop strategies for implementing a safety policy for the delivery and acceptance of COVID-19 infectious materials. Qualitative methods were used and data were collected through interviews, observations, and document review. According to the findings, the rules and guidelines to secure the delivery and acceptance of infectious materials proposed by the World Health Organizaiton, International Air Transportation Association, International Cargo Air Organization and Directorate General of Civil Aviation have still not been implemented effectively. This has been due to several inhibiting factors. It is necessary to develop a strategy in the form of policy recommendations to secure infectious materials, not only during this pandemic but also in normal conditions and in preparation for other outbreaks and pandemics. Keywords: COVID-19, delivery of infectious material, health policy, Indonesia